2013
DOI: 10.1002/acp.2979
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐examination: The Testimony of Children With and Without Intellectual Disabilities

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Cross-examination of children with and without intellectual disability 2 Permanent repository link: AbstractThe present study assessed how children with a range of cognitive abilities fared during a mock cross-examination. Ninety children (aged 4 to 11 years; 18 with intellectual disabilities [ID], 13 with borderline intellectual disabilities [BID], and 59 who were typically developing [TD]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 49 publications
2
27
0
1
Order By: Relevance
“…We expected age and memory for unchallenged responses to be negatively related to vulnerability to cross‐examination challenges, while suggestibility (measured on the GSS) would be positively related. The effects of IQ on cross‐examination challenges were harder to predict, as previous research has only assessed group differences, and not in relation to other individual difference variables (Bettenay et al, ); however, these findings are suggestive of IQ not being predictive of performance during cross‐examination. Importantly, all of our predictions were tentative given this is the first study to explore the role of these factors in relation to cross‐examination style of questioning.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…We expected age and memory for unchallenged responses to be negatively related to vulnerability to cross‐examination challenges, while suggestibility (measured on the GSS) would be positively related. The effects of IQ on cross‐examination challenges were harder to predict, as previous research has only assessed group differences, and not in relation to other individual difference variables (Bettenay et al, ); however, these findings are suggestive of IQ not being predictive of performance during cross‐examination. Importantly, all of our predictions were tentative given this is the first study to explore the role of these factors in relation to cross‐examination style of questioning.…”
mentioning
confidence: 68%
“…The sample comprised 83 children (38 males) aged 4 years 6 months to 11 years 0 months (mean = 9 years 0 months, standard deviation ( SD ) = 1 year 8 months) with a range of intellectual abilities (mean IQ= 84.64, SD = 18.54; range = 47–121). Further details concerning the characteristics and recruitment of the sample are presented by Bettenay et al ()…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Children interviewed in the direct/direct condition were equally accurate in the two interviews, whereas children in the direct/cross condition were significantly less accurate when cross‐examined. Although some researchers have shown that these effects are stronger for younger than for older children (e.g., Zajac & Hayne, ; Bettenay, Ridley, Henry, & Crane, ), Fogliati and Bussey () reported no age differences in the number of errors elicited in cross‐examinations, perhaps because the age difference between the groups was so small.…”
Section: Children's Self‐contradictions In Courtmentioning
confidence: 99%